Performance of oil palm shell lightweight aggregate concrete containing pofa as partial cement replacement towards carbonation, water absorption and corrosion - Zul Aida, Ibrahim @ Him (2014)
Palm Oil Fuel Ash (POFA) and Oil Palm shell (OPS) is q waste generated from oil palm mill which then disposed at landfill and create pollution to environment. Integration of POFA as partial cement replacement in OPS lightweight aggregate concrete(LWAC) production gives double benefit in form of cutting cost by reducing the uses of cement and reduce the ending at waste landfill in Malaysia. The present research investigates the performance of OPS LWAC containing POFA towards carbonation, water absorption and corrosion. Two types of mixes has been used in the research that the plain OPS and OPS with 20%POFA. Four types of curing methods namely water curing, spray curing, air curing and natural weather curing has been used to determine the effect of different curing methods towards carbonation and water absorption of specimen. Performance of OPS containing 20% POFA towards corrosion has been investigated using impressed voltage test method. Integrating Of 20% POFA as partial replacement by using water curing method results in lower water absorption value and carbonation. Application of water curing enable better pozzolonic reaction and produces larger amount of C-S-H gel making the concrete densçr and durable compared to normal concrete. Plain concrete and OPS LWAC with 20% POFA has shown a sign of corrosion. Both concrete the performances of both OPS and OPS with 20% POFA need to be observed for longer period of time.